1986
DOI: 10.1007/bf00392140
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ?-amylase and other gibberellin-regulated genes in aleurone tissue of developing wheat grains

Abstract: Aleurone tissue from freshly harvested immature wheat grains (Triticum aestivum L. cv. Sappo) which is normally unresponsive to gibberellic acid can be made responsive by subjecting the tissue to a pre-incubation treatment in a simple buffered medium prior to the addition of the growth substance. The effectiveness of this treatment is dependent on grain age, with grains less than 15-20 days post anthesis failing to become converted to a responsive state whilst tissue from grains older than this become increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…2). Our results are consistent with findings that a-amylase genes are not expressed in the developing seed (Nicholls 1979;Cornford et al 1986;Garcia-Maya et al 1990;Oishi and Bewley 1990). Hence, cessation of VP1 expression prior to germination may be necessary to allow induction of a-amylase genes in the germinating seed.…”
Section: Vp1 Represses A-amylase Genessupporting
confidence: 92%
See 2 more Smart Citations
“…2). Our results are consistent with findings that a-amylase genes are not expressed in the developing seed (Nicholls 1979;Cornford et al 1986;Garcia-Maya et al 1990;Oishi and Bewley 1990). Hence, cessation of VP1 expression prior to germination may be necessary to allow induction of a-amylase genes in the germinating seed.…”
Section: Vp1 Represses A-amylase Genessupporting
confidence: 92%
“…5). This suggests that expression of VP1 in the developing seed may be, at least in part, responsible for the GA insensitivity of cereal and maize a-amylase genes prior to seed maturity (Nicholls 1979;Cornford et al 1986;Garcia-Maya et al 1990;Oishi and Bewley 1990). In our experiments, VP1 displayed full repressing activity in sln mutant barley seeds (Fig.…”
Section: Interactions Between Vp1 and Plant Hormonessupporting
confidence: 49%
See 1 more Smart Citation
“…Several metabolic processes in seeds are known to be affected by dehydration, which in some cases regulates proteins at the level of gene expression (Cornford et al, 1986;Jiang and Kermode, 1994). Stages in raffinose biosynthesis might be similarly affected, although Blackman et al (1992) concluded from their studies in soybean that galactinol synthase and raffinose synthetase are not likely to be points at which regulation occurs.…”
Section: Discussionmentioning
confidence: 99%
“…When desiccation is imposed prematurely at certain stages prior to the completion of development, a switch in synthetic events is elicited; events unique to development, such as synthesis of storage protein, are terminated, and syntheses associated with germination and growth are initiated (Evans et al, 1975;Dasgupta and Bewley, 1982;Adams et al, 1983;Kermode and Bewley, 1985a, 1985b, 1986bKermode et al, 1985;Misra and Bewley, 1985;Cornford et al, 1986;Rosenberg and Rinne, 1987;Oishi and Bewley, 1992). In effecting this switch in gene expression, desiccation appears to act primarily at the transcriptional and posttranscriptional levels (Misra and Bewley, 1985;Cornford et al, 1986;Kermode et al, 1989c;Jiang and Kermode, 1994;Jiang et al, 1995aJiang et al, , 1995b. We are interested in examining events at the molecular leve1 caused by drying, which ultimately result in the off-or down-regulation of development-related genes and the onregulation of germinative and postgerminative genes.…”
mentioning
confidence: 99%